(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Kholisakhon E. Ismailova, Olga V. Bondareva (Moscow, Russian Federation) The article is devoted to the problem of preparation for the test in Russian as a foreign language for students in order to form their communication skills in social, cultural, educational and professional spheres of communication. Attention to this problem is due to the need to improve the efficiency of teaching students Russian as a foreign language for a more successful completion of the final control test. Key words: Russian as a foreign language, subtest, sample test, grammar, lexical meaning, testing on the Russian language. DOI 10.23683/1995-0640-2019-1-212-218